Notes on Pavilionis’ Idea of Nonverbal Continuum - Dagys, Jonas (Problemos, 2014)
The paper discusses the hypothesis of continuous nonverbal conceptual system, or nonverbal continuum, proposed by Rolandas Pavilionis. It attempts to provide an overview of the sources of inspiration as well as theoretical presuppositions of the hypothesis, its relation to the theory of W.V.O. Quine and contemporary frameworks of modal semantics. Finally, the status of the hypothesis against the background of analytical philosophy. It is claimed that Pavilionis’ philosophical corpus is justifiably considered as belonging to analytical tradition of philosophy with which it smoothly connects, while also, in accordance to the author’s intentions, it cannot be fitted strictly within the limits of this tradition, as it is also saturated with an urge to seek connections between analytic and hermeneutic traditions, to overcome the oft dogmatically imposed dichotomy between them.
Keywords: Rolandas Pavilionis; nonverbal continuum; meaning; semantics; analytic philosophy